2020
DOI: 10.1021/acsami.0c10397
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-Targeting and Cathepsin B-Activatable Theranostic Nanoprobe for MR/Fluorescence Imaging and Enhanced Photodynamic Therapy for Triple Negative Breast Cancer

Abstract: Because of the lack of specific targets, the highly aggressive triple negative breast cancer (TNBC) is unable to benefit from endocrine therapy or conventional targeting therapy. Even worse, current diagnostic and therapeutic approaches have limited value for TNBC. Therefore, developing TNBC-specific theranostic probes for accurate diagnosis and further selective therapy will build a powerful toolbox for TNBC management. In this contribution, we developed a sequential strategy to enhance the specificity of TNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Reproduced with permission. [ 122 ] Copyright 2020, American Chemical Society. (D) In ‐ vitro sensing ability of cathepsin B and the in ‐ vivo therapeutic applicability of 36 .…”
Section: Advances Of Enzyme‐activatable Optical Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 122 ] Copyright 2020, American Chemical Society. (D) In ‐ vitro sensing ability of cathepsin B and the in ‐ vivo therapeutic applicability of 36 .…”
Section: Advances Of Enzyme‐activatable Optical Probesmentioning
confidence: 99%
“…Considering the critical roles of cathepsin B in tumor-associated processes, a series of cathepsin Bactivatable probes have been recently reported for bioimaging or theranostics. [120][121][122][123][124] The most recently reported probes 35 and 36 are depicted in Figure 17 to elucidate the design principle, working mechanism, and performance of cathepsin Bactivatable probes.…”
Section: Cathepsin Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different types of superficial tumors, breast cancer represents the most commonly diagnosed cancer, accounting approximately for the 30% of all estimated new cancer cases globally in the female population and is regarded as the second leading cause of cancer-related mortality. [41][42][43] Based on immunohistochemistry, breast cancer can be divided into three main subtypes according to the expression of three crucial receptors, which are estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2). If the tumors do not express any of these three receptors it is the so-called triple negative breast cancers (TNBC), making it difficult to target.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent studies, including those regarding the detection of metastatic lymph nodes, 3 tumor and vessel imaging, [4][5][6] and intraoperative guidance, 7,8 have shown that biological imaging advantages significantly improves as wavelengths increase. Thus far, quantum dots, [9][10][11] carbon nanotubes, 12,13 rare earth-doped nanoparticles, 14,15 squaraine dyes, 16,17 semiconducting polymer nanoparticles, 18 and small-molecule dyes 5,19,20 have all been actively used for NIR-II imaging. The recent rapid development of small molecule dyes, in particular, has led to the use of effective probes for NIR-II fluorescence bioimaging.…”
Section: Introductionmentioning
confidence: 99%